2007
DOI: 10.1007/s11663-007-9037-2
|View full text |Cite
|
Sign up to set email alerts
|

Coating Weight Model for the Continuous Hot-Dip Galvanizing Process

Abstract: A coating weight model was developed to describe the pressure and wall shear stress distributions as functions of slot gap (d) and impingement distance (Z), for the air knife wiping of the liquid zinc coatings in continuous hot dip galvanizing at ratios of Z/d £ 8. This model was then used in validation studies in order to predict the coating weight as a function of the process parameters. The model was based on improved correlations for pressure and shear stress developed by a combination of experimental and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 16 publications
5
31
0
Order By: Relevance
“…In addition, we have used empirically determined shape functions [4], [7][8][9] for the pressure and shear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have used empirically determined shape functions [4], [7][8][9] for the pressure and shear.…”
Section: Discussionmentioning
confidence: 99%
“…In short, this suggested that there were regions in which it was possible for disturbances to grow in amplitude if a number of conditions were met. Using the empirically determined values and pressure and shear distributions from [7,8] it is possible to consider this behaviour more carefully. If we re-write (12) in the form…”
Section: Thus the Steady Solution Ismentioning
confidence: 99%
“…The time step was set at 10 −4 and the residuals was set at 10 −5 . The choice of turbulence model has been based on numerous papers [5,6], where the RNG k-ε combined to "Non-equilibrium Wall Functions" is strongly recommended. The input thickness is set by the modification of the input conditions, more exactly with the velocity inlet.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Further improvement of the model of Ellen and Tu has been the subject of more recent works. [5][6][7] Whatever their refinements, the analytical expressions of the coating thickness contain at least two jet design-dependent fitting parameters, respectively, for the pressure and shear stress distributions imposed on the strip by the impinging jet, and two physical properties of the liquid metal which are the dynamic viscosity and the density. Application of these expressions to a fitting dataset has revealed three major conceptual problems: in order to have an acceptable prediction, (1) values of the fitting parameters should fall outside their respective prescribed ranges; (2) these values depend on the coating metal, whereas AlSi-and Zn-coated strips are wiped with exactly the same knives; (3) the physical properties of AlSi take inconsistent values.…”
Section: Feed-forward Controlmentioning
confidence: 99%